2019
DOI: 10.31234/osf.io/fps6w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acting surprised: Comparing perceptions of different dynamic deliberate expressions

Abstract: People are accurate at classifying emotions from facial expressions but much poorer at determining if such expressions are genuine or deceptive. We explored if the method used by senders to produce the deceptive expression has an effect on the decoder’s ability to discriminate authenticity, drawing inspiration from two well-known acting techniques: the Stanislavski (internal) and Mimic method (external). We compared genuine surprise expressions, in response to a jack-in-the-box, to deceptive displays of sender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…For instance, the encoding-decoding perspective provides the foundation for considering genuine (i.e., innate, involuntary responses) and deliberate (i.e., voluntary, communicative signals) expressions. It is important to note, though, that the argument for clear differences in expression authenticity ( Ekman et al, 1988 ) is neither consistent with empirical investigations ( Barrett et al, 2019 ) nor reflected in human judgments of facial expressions ( Zloteanu et al, 2020 , 2018 ). First, senders seem to possess the ability to produce genuine-looking displays of emotion ( Surakka and Hietanen, 1998 ; Gosselin et al, 2010 ; Gunnery et al, 2013 ).…”
Section: The Function Of Facial Expressions: Encoding-decoding Vs Afmentioning
confidence: 88%
See 3 more Smart Citations
“…For instance, the encoding-decoding perspective provides the foundation for considering genuine (i.e., innate, involuntary responses) and deliberate (i.e., voluntary, communicative signals) expressions. It is important to note, though, that the argument for clear differences in expression authenticity ( Ekman et al, 1988 ) is neither consistent with empirical investigations ( Barrett et al, 2019 ) nor reflected in human judgments of facial expressions ( Zloteanu et al, 2020 , 2018 ). First, senders seem to possess the ability to produce genuine-looking displays of emotion ( Surakka and Hietanen, 1998 ; Gosselin et al, 2010 ; Gunnery et al, 2013 ).…”
Section: The Function Of Facial Expressions: Encoding-decoding Vs Afmentioning
confidence: 88%
“…For example, research finds no strong support for reliable muscles in either laboratory ( Krumhuber and Manstead, 2009 ) or naturalistic studies ( Fernández-Dols and Crivelli, 2013 ). Also, intensity relates more to the production method than to veracity ( Zloteanu et al, 2020 , 2018 ; Miller et al, 2020 ), and differences in the dynamic components are found to be subtle and varied between emotions ( Cohn and Schmidt, 2004 ; Namba et al, 2016 ).…”
Section: Spontaneous Vs Posed: a Sufficiently Nuanced Dichotomy?mentioning
confidence: 99%
See 2 more Smart Citations
“…Future research may benefit from examining potential limitations in the production or inhibition of the Duchenne marker in facial action tasks. Such work could shed new light on how different elicitation conditions might drive the reliability of this signal ( McCullough and Reed, 2016 ; see also Zloteanu et al, 2020 in the context of surprise expressions).…”
Section: Discussionmentioning
confidence: 99%